WaveLens: A New View onto Internet Search Results - Paek, Tim; Dumais, Susan; Logan, Ron (Proceedings of CHI '04, 2004)
Internet search results are typically displayed as a list conforming to a static style sheet. The difficulty of perusing this list can be exacerbated when screen real estate is limited. When space is limited, either, few results are seen, or result descriptions are abbreviated, making it difficult to know whether to follow a particular web link. In this paper, we describe “WaveLens,” a dynamic layout technique for displaying search results, which addresses these issues by combining a fisheye lens with progressive exposure of page content. Results from a usability study showed that participants performed faster and more accurately on a search task with one of two distinct parameter settings of WaveLens as compared to the typical static list. In a post-hoc questionnaire, participants favored that setting over both the static list and another setting which involved animated zoom. We discuss design implications for the retrieval and display of search results.